The Gut Microbiome and Schizophrenia: The Current State of the Field and Clinical Applications - Szeligowski, Tomasz; Yun, Alexandra Lim; Lennox, Belinda R.; Burnet, Philip W. J. (Frontiers in Psychiatry, 2020)
Schizophrenia is a debilitating psychiatric disorder, leading to both physical and social morbidity. Despite its importance, the aetiology of schizophrenia remains poorly understood. Furthermore, its mainstream treatments fail to address all aspects of the disorder and are associated with significant side-effects. Recently, there has been growing interest in the relationship between the gut microbiome and mental health, including in schizophrenia. In this article, we review the existing evidence implicating dysbiosis in schizophrenia and discuss how the presumed dysbiosis could fit within known hypotheses of its pathogenesis, focusing on inflammation, tryptophan metabolites, and BDNF levels. We also evaluate the clinical potential of manipulating the gut microbiome with probiotics and prebiotics as adjunctive treatments in schizophrenia, based on existing clinical and pre-clinical studies. Overall, the current data showing microbiome alterations in schizophrenia are highly discrepant and insufficient to conclude whether microbiome changes are associated with increased risk of the disorder, or are simply the result of external factors or treatment. Despite some encouraging results of pro/prebiotic supplementation, there is also inconclusive evidence for their efficacy in schizophrenia. Thus, further research and more clinical trials are needed to test the validity of manipulating the gut microbiome to improve the treatment of this disorder.